2003
DOI: 10.1097/00004356-200306000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Pain during in-patient rehabilitation after traumatic spinal cord injury

Abstract: In this prospective study, we surveyed the pain experience of 40 participants during the in-patient rehabilitation period following traumatic spinal cord injury (SCI). Twenty-eight patients (70% of the study population) had musculoskeletal (MS) pain or neuropathic (NP) pain. Pain responded positively to physical therapy and analgesics. A numerical pain scale decreased from a mean of 6.36+/-1.7 on admission to 3.2+/-1.94 on discharge (P<0.001). Paraplegic patients were more likely to have MS pain (P=0.001) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
0
3
1
Order By: Relevance
“…Werhagen et al found no statistically significant difference in neuropathic pain prevalence between tetraplegic and paraplegic patients and those with complete and incomplete lesions [19]. Other studies suggest no significant relationship between the level of injury and the presence of pain and pain severity [20,21]. When the groups with or without pain were compared, we found no Several studies have reported that the most important factor preventing daily living activities in patients with SCI is pain [19,22,23].…”
Section: Variablescontrasting
confidence: 54%
“…Werhagen et al found no statistically significant difference in neuropathic pain prevalence between tetraplegic and paraplegic patients and those with complete and incomplete lesions [19]. Other studies suggest no significant relationship between the level of injury and the presence of pain and pain severity [20,21]. When the groups with or without pain were compared, we found no Several studies have reported that the most important factor preventing daily living activities in patients with SCI is pain [19,22,23].…”
Section: Variablescontrasting
confidence: 54%
“…Some important clinical aspects, such as spasticity (Tsao and Mirbagheri, 2007) and pain (Yap et al, 2003;Jensen et al, 2007) that could influence upper limb function and motor strategies, were not assessed in this study, but it should be explored in future researches.…”
Section: Discussionmentioning
confidence: 99%
“…15 The NRS has also been shown to be sensitive to meaningful decreases in pain 16 and to changes in pain associated with treatment, such as inpatient rehabilitation. 17 Construct validity for the NRS has been established through association with negative outcomes, such as interference with basic activities of daily living, poorer psychological functioning, 18,19 self-reported difficulty in "dealing with pain," and sleep disruption 8 in persons with SCI. Consistent with these data, NRS ratings of severity have been shown to predict treatment seeking.…”
Section: Measuring Pain Intensitymentioning
confidence: 99%